2020
DOI: 10.1021/acs.analchem.9b04820
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fragmentation Techniques for the Structural Characterization of Singly Charged Agrochemicals

Abstract: Investigating the structure of active ingredients, such as agrochemicals and their associated metabolites, is a crucial requisite in the discovery and development of these molecules. In this study, structural characterization by electron-induced dissociation (EID) was compared to collisionally activated dissociation (CAD) on a series of agrochemicals. EID fragmentation produced a greater variety of fragment ions and complementary ion pairs leading to more complete functional group characterization compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…The absolute average error obtained for this molecule was 0.289 ppm. The results obtained from the 2D-EID-MS experiment are comparable to the 1D-EID tandem MS results achieved in a previous study …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The absolute average error obtained for this molecule was 0.289 ppm. The results obtained from the 2D-EID-MS experiment are comparable to the 1D-EID tandem MS results achieved in a previous study …”
Section: Resultssupporting
confidence: 88%
“…The results obtained from the 2D-EID-MS experiment are comparable to the 1D-EID tandem MS results achieved in a previous study. 37 Internal Calibration of 2D. The pirimiphos-methyl fragmentation line was used to internally calibrate the 2DMS spectrum, resulting in spectrum-wide subppm accuracy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The individual spectra were internally calibrated, using the product ions of these species labeled in the SI, to achieve sub-ppm accuracy. Elemental compositions, and thus cleavages, were assigned by the same procedure described previously …”
Section: Experimental Methodsmentioning
confidence: 99%
“…These proof-of-concept experiments demonstrated that EID and CID fragment ions can differ and that the additional EID fragment ions facilitate analyte identifications. In a recent study by Marzullo et al, the benefits of EID for metabolite structure elucidation for a set of seven agrochemicals were impressively showcased [42]. A representative example comparing CID (or collision-activated dissociation, CAD) and EID mass spectra of protonated azoxystrobin, a commonly used fungicide, is shown in Fig.…”
Section: Electron-based Fragmentationmentioning
confidence: 99%
“…With the aid of nanosecond pulsed solid-state and gas-phase laser systems, which offer energies up to 150 J/pulse and often operate at 157 nm, 193 nm, 213 nm, 248 nm, 266 nm, 337 nm, 351 nm, and 355 nm with repetition rates between 10 and 5000 Hz, many metabolite and lipid ions are readily activated in the gas phase. In the IR region especially O-H, N-H, C=O, and P-O, valence [42], copyright 2020 American Chemical Society. (ii) EID-MS 2 of protonated (blue) PC 16:1(9Z)/16:1(9Z) and (purple) PC 16:1(9E)/16:1(9E).…”
Section: Photon-based Fragmentationmentioning
confidence: 99%